INVESTIGATING THE ICT TOOLS AND PLATFORMS USED BY THE ENGLISH TEACHERS IN EFL CLASSROOMS - Mustasyfa Thabib Kariadi; Syifa Islamiati; Dian Adiarti (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
The development of ICT (Information and Communication Technology) significantly influences the educational landscape. In post-pandemic setting, the integration of ICT becomes essential in supporting the effectiveness of teaching and learning processes. This research aimed to: (1) identify the ICT tools and platforms used by the English teachers; (2) investigate the challenges faced by the teachers; and (3) explore the teachers’ responses to the use of ICT tools and platforms in EFL classrooms. The research employed a descriptive-qualitative method, with data collected through non-participant classroom observations and semi-structured interviews with three English teachers. Based on observations and interviews, The findings revealed that: (1) the ICT tools and platforms used by the English teachers included laptops, LCD projectors, speakers, PowerPoint, Wordwall, Liveworksheet, Quizizz, Kahoot, Canva, and Learn English Kids; (2) the challenges faced by the teachers included a lack of confidence and limited experience in using specific platforms at the teacher level, while the school level challenges included limited facilities, technical issues, electricity problems, and time constraints; and (3) the strategies implemented by the teachers to overcome these challenges involved bringing personal equipment, using a whiteboard as a projector screen, conducting ice-breaking activities during technical delays, and participated in training or self-learning to improve their ICT skills. Thus, the effective use of ICT in EFL instruction relies on adequate infrastructure, teacher readiness, and a supportive learning environment for the development of more effective and contextually appropriate ICT integration strategies.